Ende Rahim Pancasila: Embrio Pancasila dalam Nilai-nilai Budaya Masyarakat Ende-Lio - Adrianus Yohanes Mai; Amandus Benediktus Seran Klau; Otto Gusti Ndegong Madung (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Pancasila is the crystallization of the values of culture, religion and customs of the Indonesian nation. Knowing the history of its birth and also the socio-cultural bedground are essential to fully understand Pancasila. Ende is a historical place because it was in this place where Sukarno contemplated the Indonesian values that was revealed in Pancasila. This study analyzes how the values of the Ende-Lio cultural community as the embryo of the birth of Pancasila. The method used in this study is a qualitative ethnographic method in which five points of Pancasila are analyzed based on the cultural values of the Ende-Lio community. Based on this study, it can be concluded that every item of Pancasila is basically contained in the cultural values of the Ende-Lio community.